Malaria parasite centrins can assemble by Ca2+-inducible condensation - Voss, Yannik; Klaus, Severina; Lichti, Nicolas; Ganter, Markus; Guizetti, Julien (PLoS pathogens, 2023)
Centrins are small calcium-binding proteins that have a variety of roles and are universally associated with eukaryotic centrosomes. Rapid proliferation of the malaria-causing parasite Plasmodium falciparum in the human blood depends on a particularly divergent and acentriolar centrosome, which incorporates several essential centrins. Their precise mode of action, however, remains unclear. In this study calcium-inducible liquid-liquid phase separation is revealed as an evolutionarily conserved principle of assembly for multiple centrins from P. falciparum and other species. Furthermore, the disordered N-terminus and calcium-binding motifs are defined as essential features for reversible biomolecular condensation, and we demonstrate that certain centrins can form co-condensates. In vivo analysis using live cell STED microscopy shows liquid-like dynamics of centrosomal centrin. Additionally, implementation of an inducible protein overexpression system reveals concentration-dependent formation of extra-centrosomal centrin assemblies with condensate-like properties. The timing of foci formation and dissolution suggests that centrin assembly is regulated. This study thereby provides a new model for centrin accumulation at eukaryotic centrosomes.
Gesehen am 20.08.2024
Im Titel ist 2+ hochgestellt